Examining neurodevelopmental problems in 15q11.2 (BP1‐BP2) copy number variation carriers at ages 9/12 and 18 in a Swedish twin sample - Lina Jonsson; Joanna Martin; Paul Lichtenstein; Patrik K. E. Magnusson; Sebastian Lundström; Lars Westberg; Kristiina Tammimies (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Several copy number variations (CNVs) are associated with increased risk for neurodevelopmental and psychiatric disorders. The CNV 15q11.2 (BP1‐BP2) deletion has been associated with learning difficulties, attention deficit hyperactivity disorder (ADHD), epilepsy, and brain morphology; however, many carriers present mild or no symptoms. Carrying the reciprocal duplication does not seem to confer risk for these disorders or traits. Our aim was to examine the impact of carrying either 15q11.2 deletion and reciprocal duplication on neurodevelopmental problems in a population‐based sample of children. Methods Twins with genotype and phenotype information in the Child and Adolescent Twin Study in Sweden (CATSS) were included (N = 12,040). We included measures of neurodevelopmental problems (NDPs), including learning problems, from the questionnaire Autism–Tics, ADHD, and other Comorbidities inventory (A‐TAC) at age 9/12, ADHD and autism spectrum disorder (ASD) questionnaires at age 18, as well as information about lifetime psychiatric diagnoses and epileptic seizures. We tested the association between these phenotypic measurements and carrying the 15q11.2 deletion, the reciprocal duplication, and other CNVs with previously reported strong associations with neurodevelopmental and psychiatric disorders (i.e., psychiatric CNVs). Results We identified 57 carriers of the 15q11.2 deletion, 75 carriers of the reciprocal duplication, and 67 carriers of other psychiatric CNVs. We did not find an increased risk for NDPs or psychiatric diagnoses in the 15q11.2 deletion carriers. For 15q11.2 duplication carriers, we found an increased risk for math learning problems and fewer self‐reported ADHD symptoms at age 18 but not for other NDPs. In line with previous studies, we found an increased risk of NDPs and other evaluated phenotypes in carriers of psychiatric CNVs. Conclusions Our results support previous findings that carrying 15q11.2 deletion does not have a large effect on NDPs in children.